TYPOLOGY AND FORMS OF LITERARY RELATIONS IN COMPARATIVE EASTERN AND WEST LITERATURE - Vakhidova Mushtariy Uktamovna (Western European Studies, 2025)
Literary relations between Eastern and Western literatures have historically been a multi-layered and complex process, a direct expression of intercultural communication. This study analyzes the commonalities and differences that have arisen in literary processes not only at the level of external forms, but also at the level of artistic and aesthetic thinking, poetics, genre systems and typology of images. The purpose of the work is to scientifically and theoretically illuminate the typology and forms of literary relations in comparative literature of the East and the West and to identify their historical foundations. The research used comparative-historical, typological, hermeneutic, intertextual and reception theory methods. The views of such scholars as A. N. Veselovsky, V. M. Zhirmunsky, N. I. Konrad, A. Dima, D. Dyurishin were taken as a methodological basis, and the processes of translation and adaptation, the phenomena of dedication, patronage and court patronage were considered as important forms of interliterary relations. As a result, three main types of literary connections - contact-genetic connections, typological parallels and historical-genetic connections - were identified, and their historical-real foundations were scientifically substantiated on the example of the Great Silk Road, the Andalusian literary environment, the Eastern Renaissance and the European Renaissance. The study shows that a deep study of the literary connections of the East and the West allows us to interpret the national literary heritage in an international context, periodize literary processes, identify translation and reception mechanisms and strengthen them theoretically. Therefore, comparative literature today occupies an important place in the system of modern sciences, serving to further expand intercultural dialogue
Keywords: comparative literary studies; East and West; literary relations